Diseño de un plan de negocios para abrir una empresa de explotación ganadera doble propósito en Bosconia (2021)
This project proposes the design of a business model for the opening of a company dedicated to the exploitation of Cebu Brahman cattle, through the implementation of a dual-purpose model with a silvopastoral system. This project will be carried out at the El Líbano farm, located in the rural area of the Bosconia municipality, in the Cesar department. The conditions found in this location are adequate for the development of the present given the fertility of the land, large areas of land and the climatic conditions. The constitution of a simplified joint stock company is explored because it is the one that adapts to the needs of this project.